STRATEGI PEMBERDAYAAN MASYARAKAT BERBASIS KEMITRAAN MULTIPIHAK DALAM PENGELOLAAN SAMPAH RUMAH TANGGA DI DESA MARGAGIRI KECAMATAN BOJONEGARA KABUPATEN SERANG - Fakhri, Akhmad; Siregar, Herlina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Waste management is currently a problem in every region of Indonesia, including the village of Margagiri in Bojonegara Subdistrict, Serang Regency, Banten Province. This is due to a lack of proper waste management. To address this issue, a company in the vicinity of the village—PT PLN Indonesia Power UBP Cilegon, has launched a community empowerment program with one of its focuses on waste management. In carrying out these empowerment activities, PT PLN Indonesia Power UBP Cilegon does not operate alone but collaborates with multi-stakeholder partners. Therefore, the objective of this study is to provide an overview of how community empowerment strategies based on multi-stakeholder partnerships are implemented.The research methodology employed a descriptive qualitative approach. The results of this study indicate that the multi-stakeholder empowerment strategy consists of the initiation, formation, implementation, evaluation, and development stages. The partnership has been successful due to the active involvement of various actors and the achievement of partnership success indicators.